Designing Human Health Risk Management Model for Dam Construction Projects - R. Ghorbanalipour; AM. Ahmadvand; M. Ahmadvand; H. Eghbali (Civil Engineering Journal, 2018)
Identifying the risks of dam construction projects due to their high importance in terms of utilization, the amount of investment they invest in, the location of the region, the nature of the complexity of the project, and the presence of many uncertainties, including natural disasters and costs High builds are of special importance. Selection and implementation of the project with the least risk can lead to economic savings, optimal use of resources, increased productivity, flood control and supply of drinking water, agriculture and industry. Based on the results of this study, the "human factors" factor in the probability of occurrence and outcome in the category of severity of risk was the highest score among the indicators related to risk factors assessment of dam construction projects. In this research, first, identify the main risks of the project through a questionnaire and then identify the response strategies for the most critical risks, and finally, with the help of the decision model, prepare and, through paired comparisons, the best strategy for the most important human risk factors in the Polrood dam project is selected. In order to assess the risk in the dam, the risk parameters were identified and prioritized in different stages of the project, as well as 16 sub-subsets in four categories of risk factors: human, technical-environmental, environmental and psychological factors, and using the method DEMATEL-ANP were evaluated and ranked. "The lack of sufficient training to use devices and tools" was the most critical.